Dermatophilus congolensis. III. Behaviour in relation to oxygen - Cruz, Luiz Celso Hygino da (Pesquisa Agropecuaria Brasileira, 2014)
The sensibility of Dermatophilus congolensis to oxygen and its redox potential were studied using "shake tubes" with brain and heart infusion agar. The microbe was shown to be microaerophilic, not growing under strictly anaerobic conditions. It was verified, starting with small inoculations, that the microorganism did not grow when the Eh was above 0.150 v.